Kyai and Pesantren in the Islamic Historiography of Indonesia - Sulasman, Sulasman (TAWARIKH, 2012)
ABSTRACT: Diversity in the writing of history is not just about the topic but also about the object of study or research in the historical writing.Â Spanning the history of the Muslim community in Indonesia was started since the vast stretches of the Islamization process and economic and political power were formed to the resistance movement against the occupation of Western nations with a peak of Indonesiaâs independence declaration.Â Therefore, in the historiography of the Islamic community in Indonesia is very improbable that the historians with all their limitations are able to describe or reconstruct the whole history of Muslims from the beginning until now.Â Nevertheless, the works of the writing on the history of Islam in Indonesia have been widely written, both by Indonesian and foreign writers.Â One important thing about the history of Islam in Indonesia is analyzing the roles and position of âpesantrenâ (Islamic boarding schools), âkyaiâ (Islamic religious scholars), and âsantriâ (Islamic students in boarding school).Â Therefore, if we discuss about resistance movement against the Western penetration in Indonesian history, there are many events related to the resistance movement of the Islamic society. KEY WORDS: The roles of kyai, pesantren, santri, Indonesian historiography, Islamic society, and diversity in history.About the Author: Dr. Sulasman is a Senior Lecturer at the Department of Islamic History and Civilization, Faculty of Adab and Humanities UIN (Universitas Islam Negeri or State Islamic University) Sunan Gunung Djati, Jalan Jenderal A.H. Nasution No.105 Cipadung, Bandung 40614, West Java, Indonesia. He can be reached at: sulasman14@yahoo.comHow to cite this article? Sulasman. (2012). âKyai and Pesantren in the Islamic Historiography of Indonesiaâ in TAWARIKH: International Journal for Historical Studies, Vol.4(1) October, pp.67-82. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 5, 2012); Revised (September 9, 2012); and Published (October 28, 2012).